INTERAGENCY COLLABORATION AND SECURITY CHALLENGES - Ben Maure (The Journal of Intelligence, Conflict and Warfare, 2025)
On November 19th, 2024, Superintendent Ben Maure presented Interagency Collaboration in Security and Policing at this year’s West Coast Security Conference. The presentation was followed by a question-and-answer period with questions from the audience and CASIS Vancouver executives. The key points discussed were Supt. Maure's work on international child exploitation, the security and legitimacy gaps in Haiti, and the need for better interagency cooperation and information sharing in Canada.